2019
DOI: 10.3389/fgene.2019.00377
|View full text |Cite
|
Sign up to set email alerts
|

The Sterility of Allotriploid Fish and Fertility of Female Autotriploid Fish

Abstract: Based on the formation of an autotetraploid fish line (4nAUT, 4n = 200; F 2 –F 11 ) derived from the distant hybridization of female Carassius auratus red var. (RCC, 2n = 100) × male Megalobrama amblycephala (BSB, 2n = 48), we produced autotriploid hybrids (3nAUT) by crossing females of RCC with males of 4nAUT and allotriploid hybrids (3nALT) by crossing females of Cyprinus carpio (CC, 2n = 100) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For example, the triploid fish has been produced by the hybridization of the white crucian carp (C. cuvieri, 2n = 100, ♀) and the allotetraploid hybrids (4n = 200, ♂) (Liu et al 2001, Guo et al 2006. Additionally, autotriploid fish has been produced by the crossing of red crucian carp (2n = 100, ♀) and autotetraploid hybrids (4n = 200, ♂), and allotriploid hybrids has been produced by the hybridization of common carp (2n = 100, ♀) and autotetraploid hybrids (4n = 200, ♂) (Hu et al 2019).…”
Section: Genetic Rules At the Chromosome Levelmentioning
confidence: 99%
“…For example, the triploid fish has been produced by the hybridization of the white crucian carp (C. cuvieri, 2n = 100, ♀) and the allotetraploid hybrids (4n = 200, ♂) (Liu et al 2001, Guo et al 2006. Additionally, autotriploid fish has been produced by the crossing of red crucian carp (2n = 100, ♀) and autotetraploid hybrids (4n = 200, ♂), and allotriploid hybrids has been produced by the hybridization of common carp (2n = 100, ♀) and autotetraploid hybrids (4n = 200, ♂) (Hu et al 2019).…”
Section: Genetic Rules At the Chromosome Levelmentioning
confidence: 99%
“…Xiao et al [ 25 ] reported that triploid Carassius auratus in Dongting water system produces normal gametes. Hu et al [ 26 ] reported that female autotriploid hybrids (3nAUT) generated by crossing females of Carassius auratus red var. with males of autotetraploid fish produced mature eggs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we artificially obtained fertile allotetraploids (4nRB, 4n = 148, F 1 ) from the distant hybridization of 2nRCC (♀) × BSB (♂) ( Liu et al, 2007 ). The fertile 4nRCC (4n = 200) was obtained through the fertilization of diploid sperm and eggs caused by the abnormal chromosome behavior during meiosis of 4nRB, and the 4nRCC lineage (F 2 –F 14 ) was established through continuous self-crossing ( Qin et al, 2014 ; Hu et al, 2019 ). The newly synthesized 4nRCC possessed four sets of chromosomes from 2nRCC and produced diploid gametes, and there were obvious phenotypic differences between 2nRCC and 4nRCC ( Qin et al, 2014 ; Qin Q. et al, 2018 ; Qin Q.…”
Section: Introductionmentioning
confidence: 99%